Effectiveness of transcranial electrical stimulation combined with dual-task training in stroke, mild cognitive impairment and Parkinson’s disease: a systematic review and meta-analysis of randomized controlled trials - Fu, Yutong; Wang, Wenli; Yan, Qianxi; Zhu, Chang; Chai, Siaw Chui; Subramaniam, Ponnusamy; Yao, Liqing; Singh, Devinder Kaur Ajit (Frontiers in Human Neuroscience, 2026)
AimIn this systematic review and meta-analysis, we evaluated the effectiveness of transcranial direct current stimulation (tDCS) and transcranial alternating current stimulation (tACS) or transcranial random noise stimulation (tRNS) combined with dual task training (DTT) on physical and cognitive functions in adults with mild cognitive impairment (MCI), Parkinson’s disease (PD), and stroke disorders.MethodWe conducted a systematic search of the Web of Science, MEDLINE, Cochrane Library, PubMed, and CINAHL databases for English-language literature on randomized clinical trials (RCTs) investigating the effects of tDCS, tACS, or tRNS combined with DTT in adults with MCI, PD, and stroke. The search covered studies from the inception of each database up to November 21, 2025. The initial screening of selected articles was conducted independently by two researchers (YLQ and WLW).ResultsA total of twelve studies met the inclusion criteria, comprising individuals with stroke (n = 4), MCI (n = 3), and PD (n = 5). Meta-analysis revealed that active tDCS+DTT yielded no significant overall improvement in global cognition (Montreal Cognitive Assessment (MoCA): SMD = 0.09, 95% CI [−0.49, 0.66], p = 0.77, I2 = 72%). A large, highly homogeneous benefit was observed for executive function (TMT-B: SMD = −1.33, 95% CI [−2.39, −0.27], p = 0.01), driven exclusively by the MCI subgroup (SMD = −2.35, 95% CI [−3.20, −1.51], I2 = 0%). Timed Up and Go cognitive-motor dual-task (TUG CMDT) cadence improved overall (SMD = 0.58, 95% CI [0.09, 1.08], p = 0.02, I2 = 39%) in both MCI and stroke subgroups. TUG motor dual task (MDT) speed improved modestly (SMD = 0.42, 95% CI [0.02, 0.83], p = 0.04, I2 = 34%), and CMDT speed showed a strong trend (SMD = −0.49, p = 0.09), only significant in stroke (SMD = −1.42, p = 0.002). However, this generalized finding must be nuanced by specific efficacy observed in individual PD studies, which reported significant gains in force-tremor decoupling, postural stability, and CMDT accuracy.ConclusionThe meta-analysis suggests that the effects of tDCS combined with DTT are remarkable in certain populations and for specific outcomes. While substantial improvements are confirmed for executive function and dual-task gait in MCI and stroke, the overall limited efficacy in PD highlights the critical influence of heterogeneity and intervention specificity. Future research should prioritize disease-specific electrode montages and the integration of tACS or tRNS to optimize outcomes across diverse neurological populations.